2019
DOI: 10.1161/atvbaha.119.311392
|View full text |Cite
|
Sign up to set email alerts
|

2018 George Lyman Duff Memorial Lecture

Abstract: Recent studies have led to a broader understanding of the genetic architecture of coronary artery disease and demonstrate that it largely derives from the cumulative effect of multiple common risk alleles individually of small effect size rather than rare variants with large effects on coronary artery disease risk. The tools applied include genome-wide association studies encompassing over 200 000 individuals complemented by bioinformatic approaches including imputation from whole-genome data sets, expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…McPherson defined that the genetic architecture of CAD is mostly driven by the combined impact of numerous common variants, each of which contributes little to disease risk when considered separately. This is in contrast to rare variants having significant influences on the incidence of coronary disease [ 18 ]. The identification of these common variations follows the publication of massive genome-wide association studies (GWAS) on a bigger view [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…McPherson defined that the genetic architecture of CAD is mostly driven by the combined impact of numerous common variants, each of which contributes little to disease risk when considered separately. This is in contrast to rare variants having significant influences on the incidence of coronary disease [ 18 ]. The identification of these common variations follows the publication of massive genome-wide association studies (GWAS) on a bigger view [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these clinical risk factors, genetic risk scores, often referred to as polygenic risk scores (PRSs), have been shown to independently predict the development of CAD [2][3][4][5][6] . The potential use of genetic data in clinics is based on robust evidence and the importance of family history, with an estimated 40%-60% CAD heritability 6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…Risk prediction for CHD using PRS has been extensively studied over the past 10 to 15 years . The biological plausibility and potential clinical utility of PRS in CHD is rooted in the importance of family history, with estimates of heritability of CHD of up to 50% . However, family history is often not well captured and is a crude measure of inherited risk.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, most people do not harbor a known pathogenic or disease-causing rare variant in a single gene that can account for the familial risk. Genome-wide association studies have identified at least 160 SNVs that may each contribute to the overall risk of CHD, but individually have small effect sizes. Advances in whole-genome sequencing as well as improved computing capabilities have allowed the derivation of PRSs that contain millions of SNVs.…”
Section: Introductionmentioning
confidence: 99%